Urgensi Pengaturan tentang Pemenuhan Hak dan Kebutuhan Dasar Perempuan di Lembaga Pemasyarakatan - Yustina Mariana Neta; Heri Fernandez Butar-Butar (Indonesian Journal of Social Science Education (IJSSE), 2022)
Human rights are fundamental rights that must be given by the state to its citizens, including prisoners. The granting of these rights must of course be fair and proportional. This study aims to see and find out how to fulfil the special needs of female inmates in the Penitentiary, considering that women have specific characteristic according to their nature, namely menstruation, pregnancy, childbirth and breastfeeding. With knowledge about the special needs of female prisoners in prison, it is possible to formulate special policies or regulation that dea; with and overcome these problems . In this case, more sensitive correctional policies and institutional rules related to gender issues are needed to ensure the fulfillment of the needs of female prisoners. Based on the research , it is stated that Indonesia is one of the countries that agrees to the Bangkok Rules, which recognizes that women in the criminak justice system have special needs, but their implementation has not been maximized so that optimization is needed in their handling. The research method sed is literature review, by tracing related research to strengthen the research results. Based on the results of the study, it is known that the implementation of meeting the needs for female prisoners is still not uniform in all Correctional Technical Implementation Units, because ther is no national policy in Indonesia that legally and specifically regulates female prisoners.